Preparedness for inclusive education in early childhood Development (ECD): a survey of Gweru district ECD centres - Nomatter Manzunzu; Onias Mutovosi (International Journal of Education Humanities and Social Science, 2023)
This study qualitatively examines through descriptive survey, the state of preparedness for the adoption of Inclusive Education (IE) among Gweru district ECD centres. The paradigm shift towards IE has become a central concern within Zimbabwe’s education at all educational levels although adoption of IE at ECD level remains a challenge. Yet, the horizon of accessing and delivering quality and sustainable early childhood education that can transform schools and communities into ‘The Future We Want’ seems elusive. Ten ECD teachers and five school heads were purposively selected in the study. Observation checklists, interviews and surveys were administered for data gathering. The study revealed that ECD centres do not have infrastructure that adequately responds to the diverse needs of learners. It also emerged that ECD centres have capacity building projects such as nutrition gardens and toy production to assist learners from poor socio-economic backgrounds. The study recommends that the government should increase staff development workshops for ECD teachers and administrators.